PRECLINICAL TEST CONDENSED TANNINS OF Pluchea indica DOSAGE BASED ON BEHAVIOURAL PARAMETERS OF MALE Rattus norvegicus AS CONTRACEPTIVE CANDIDATE - Hanifa Rizky Rahmawati; Eko Susetyarini; Fendy Hardian Permana (LP4MK STKIP PGRI Lubuklinggau, 2022)
Herbal medicine's development as an antifertility agent is the condensed tannins of the leaves of beluntas (Pluchea indica). This study was to determine the safety of P. indica condensed tannin extract based on the behaviour of male Rattus norvegicus. This research design was qualitative descriptive with two weeks direct observation of animal models and scoring based on rats' behaviour parameters. Comparative research involving 24 white male rats based on negative control group (aquades), dose groups : I (0.4 ml/KgBW), II (2 ml/KgBW), and III (2 ml/KgBW and 3 ml/KgBW). Parameters observed were body posture, motoric activity, ataxia, righting reflex, gauze test, analgesia, ptosis, and respiratory death or cardiac arrest. The result showed a significant correlation between three of the eight parameters, namely body posture, motor activity, and ptosis based on the dose that had been given. The safe dossage as an antifertility candidate for humans was range I to dose II (0.4ml/KgBW-2 ml/KgBW) because it was included in the practically non-toxic category. Therefore, this research was important to make condensed tannins safe in their application as an antifertility drug for humans in the future.